Synthesis and Characterization of New Polyesters Derived From 4, 4'-Azodibenzoic Acid, Malic Acid and Adipic Acid With Aromatic Diols - Mutar , Mohammed A. (Iraqi Journal of Science, 2022)
A series of new aromatic polyesters have been synthesized by polycondensation of different aromatic diols (M1, M2 ,M3) with different dicarboxlic acids (4,4'azo di benzoic acid, malic acid and adipic acid) using dibutyltine dilaurate as catalyst . The preparation of thermally stable polyesters was successfully applied with good yields (60-85%). All polyesters (PE1-PE4) containing aliphatic methylene linkage, and azo group in the main chain. The resulted polymers are readily soluble in aprotic polar solvents , such as (pyridine , CHCl3 , CH2Cl2 , NaOH , H2SO4 , HNO3 , acetone , benzene , DMF , DMSO , THF) without need for heating. Thermal analysis of polyesters by Thermo Gravimetric Analysis (TGA) reveals that these aromatic polyesters possess thermal stability. Monomers and polyesters were characterized by FT-IR and1HNMR spectroscopies.